2015
DOI: 10.3390/molecules200815359
|View full text |Cite
|
Sign up to set email alerts
|

Phenyllactic Acid from Lactobacillus plantarum PromotesAdipogenic Activity in 3T3-L1 Adipocyte via Up-Regulationof PPAR-γ2

Abstract: Synthetic drugs are commonly used to cure various human ailments at present. However, the uses of synthetic drugs are strictly regulated because of their adverse effects. Thus, naturally occurring molecules may be more suitable for curing disease without unfavorable effects. Therefore, we investigated phenyllactic acid (PLA) from Lactobacillus plantarum with respect to its effects on adipogenic genes and their protein expression in 3T3-L1 pre-adipocytes by qPCR and western blot techniques. PLA enhanced differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…Especially, these strains were reported to posses the down regulation of the risk of cardiovascular diseases (Ahren et al, 2014), produce pro-inflammatory cytokines in the intestinal epithelial cells (Murofushi et al, 2015), produce varied concentrations of exopolysaccharide with anticancer property (Wang et al, 2014), reduce kidney stones (Sasikumar et al, 2014), enhance splenocytes in dendritic cells (Ku et al, 2014) and reduce the cholesterol level in the adipose tissue (Li et al, 2014. Recently, Ilavenil et al (2015) claimed that the phenyl lactic acid recovered from L. plantarum promotes adipogenic activity in 3T3-L1. Interestingly, L. plantarum significantly induces mucosal, humoral and cellular immune responses (Shi et al, 2014) and protects against symptoms of irritable bowel syndrome (Stevenson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Especially, these strains were reported to posses the down regulation of the risk of cardiovascular diseases (Ahren et al, 2014), produce pro-inflammatory cytokines in the intestinal epithelial cells (Murofushi et al, 2015), produce varied concentrations of exopolysaccharide with anticancer property (Wang et al, 2014), reduce kidney stones (Sasikumar et al, 2014), enhance splenocytes in dendritic cells (Ku et al, 2014) and reduce the cholesterol level in the adipose tissue (Li et al, 2014. Recently, Ilavenil et al (2015) claimed that the phenyl lactic acid recovered from L. plantarum promotes adipogenic activity in 3T3-L1. Interestingly, L. plantarum significantly induces mucosal, humoral and cellular immune responses (Shi et al, 2014) and protects against symptoms of irritable bowel syndrome (Stevenson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years an attempt has been made to analyze the health benefits of host organisms by improving the balance of gut microbial flora, reducing cholesterol, vitamin production providing immunomodulatory effects and regulating lactase activity and various metabolic processes. The bacteria from the genera, Bifidobacterium and Lactobacillus are widely reported probiotic culture, however the genera such as, Saccharomyces , Enterococcus , Streptococcus and Lactococcus are commonly used as probiotics ( García-Ruiz et al, 2014 , Ilavenil et al, 2015a , Valan Arasu et al, 2013 ). The potential health benefits of probiotics on host health namely, production of anti-microbial metabolites and synthesis of B-group vitamins, anti-obesity effect ( Kim et al, 2018 ), anti-diabetic effect, cholesterol-lowering effect and oxidative stress down-regulation ( Yadav et al, 2018 ) have been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Lab. plantarum has been reported to inhibit the differentiation and lipid accumulation in adipocytes by downregulating expression of PPARγ, C/EBPα, FAS, aP2, leptin, GPDH, and CD36 (Ilavenil et al, 2015; Park et al, 2013b; Park et al, 2018). Administration of Lab.…”
Section: Introductionmentioning
confidence: 99%